Translucency and color match with a shade guide of esthetic brackets with the aid of a spectroradiometer - Yong-Keun Lee; Yu Bin (Dental Press Editora, 2016)
ABSTRACT Objective: Since the color of esthetic brackets should match that of teeth, the aims of this study were to determine the color and translucency of esthetic brackets by means of the clinically relevant use of a spectroradiometer, and to compare the color of brackets with that of a commercial shade guide. Methods: The color of central and tie-wing regions of four plastic and four ceramic brackets was measured according to the CIE L*a*b* color scale over white and black backgrounds. Brackets were classified into five groups based on their composition. The color of Vitapan Classical Shade Guide tabs was also measured. Translucency parameter (TP) and contrast ratio (CR) were calculated to determine translucency. Results: Color differences between brackets and the shade guide tabs were 10.4 - 34.5 ∆E*ab units. TP and CR values for the central region were 16.4 - 27.7 and 0.38 - 0.58, whereas for the tie-wings they were 24.0 - 39.9 and 0.25 - 0.45, respectively. The color coordinates, TP and CR values were significantly influenced by bracket composition and brand (p < 0.05). Conclusions: Esthetic brackets investigated herein showed unacceptable color differences (∆E*ab > 5.5) compared with the shade guide tabs. Differences in the translucency of brackets by brand were within the visually perceptible range (∆CR > 0.07). Therefore, brackets showing the best matching performance for each case should be selected considering esthetic and functional demands.